Comparison of Third-Generation Sequencing and Routine Polymerase Chain Reaction in Genetic Analysis of Thalassemia - Xu, Zhen; Hu, Lanping; Liu, Yinyin; Peng, Can; Zeng, Guo; Zeng, Li; Yang, Mengyue; Linpeng, Siyuan; Bu, Xiufen; Jiang, Xuanyu; Xie, Tiantian; Chen, Libao; et al. (Archives of pathology & laboratory medicine (1976), 2024)
Thalassemia is the most widely distributed monogenic autosomal recessive disorder in the world. Accurate genetic analysis of thalassemia is crucial for thalassemia prevention. To compare the clinical utility of a third-generation sequencing-based approach termed comprehensive analysis of thalassemia alleles with routine polymerase chain reaction (PCR) in genetic analysis of thalassemia and explore the molecular spectrum of thalassemia in Hunan Province. Subjects in Hunan Province were recruited, and hematologic testing was performed. Five hundred four subjects positive on hemoglobin testing were then used as the cohort, and third-generation sequencing and routine PCR were used for genetic analysis. Of the 504 subjects, 462 (91.67%) had the same results, whereas 42 (8.33%) exhibited discordant results between the 2 methods. Sanger sequencing and PCR testing confirmed the results of third-generation sequencing. In total, third-generation sequencing correctly detected 247 subjects with variants, whereas PCR identified 205, which showed an increase in detection of 20.49%. Moreover, α triplications were identified in 1.98% (10 of 504) hemoglobin testing-positive subjects in Hunan Province. Seven hemoglobin variants with potential pathogenicity were detected in 9 hemoglobin testing-positive subjects. Third-generation sequencing is a more comprehensive, reliable, and efficient approach for genetic analysis of thalassemia than PCR, and allowed for a characterization of the thalassemia spectrum in Hunan Province.